Handbook of research on challenges for human resource management in the COVID-19 era - Figueiredo, Paula Cristina Nunes, 1978-; Tome, Eduardo Luis de Campos, 1964-; Rouco, Josè Carlos Dias (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"This reference book analyzes the state of the art of human resources management in a digital transformation context, investigating the factors that promote more learning and development dynamics in organizational contexts, and organizational systems, processes, and practices for learning and human resources development in organizations"--